Plant Derived Aporphinic Alkaloid S-(+)-Dicentrine Induces Antinociceptive Effect in Both Acute and Chronic Inflammatory Pain Models: Evidence for a Role of TRPA1 Channels - Montrucchio, Deise Prehs; Córdova, Marina Machado; Soares Santos, Adair Roberto (PLOS ONE, 2013)
S-(+)-Dicentrine is an aporphinic alkaloid found in several plant species, mainly from Lauraceae family, which showed significant antinociceptive activity in an acute model of visceral pain in mice. In this work, we extended the knowledge on the antinociceptive properties of S-(+)-dicentrine and showed that this alkaloid also attenuates mechanical and cold hypersensitivity associated with cutaneous inflammation induced by Complete Freund’s Adjuvant in mice. Given orally, S-(+)-dicentrine (100 mg/kg) reversed CFA-induced mechanical hypersensitivity, evaluated as the paw withdrawal threshold to von Frey hairs, and this effect lasted up to 2 hours. S-(+)-Dicentrine also reversed CFA-induced cold hypersensitivity, assessed as the responses to a drop of acetone in the injured paw, but did not reverse the heat hypersensitivity, evaluated as the latency time to paw withdrawal in the hot plate (50°C). Moreover, S-(+)-dicentrine (100 mg/kg, p.o.) was effective in inhibit nociceptive responses to intraplantar injections of cinnamaldehyde, a TRPA1 activator, but not the responses induced by capsaicin, a TRPV1 activator. When administered either by oral or intraplantar routes, S-(+)-dicentrine reduced the licking time (spontaneous nociception) and increased the latency time to paw withdrawal in the cold plate (cold hypersensitivity), both induced by the intraplantar injection of cinnamaldehyde. Taken together, our data adds information about antinociceptive properties of S-(+)-dicentrine in inflammatory conditions, reducing spontaneous nociception and attenuating mechanical and cold hypersensitivity, probably via a TRPA1-dependent mechanism. It also indicates that S-(+)-dicentrine might be potentially interesting in the development of new clinically relevant drugs for the management of persistent pain, especially under inflammatory conditions.